Bacterial isolation from environment and nosocomial pathogens in burned patient, with their susceptibility pattern in burn and plastic surgery department, Aljalla Hospital Benghazi - Mohammed Idres El Hassy; Suad El Senussi; khaled elgazwi (Journal of Surgery and Surgical Research - Peertechz Publications, 2018)
Background: Hospital environment is a potential reservoir of bacterial pathogens, therefore Burn patients are at high risk of developing nosocomial infection because of their destroyed skin barrier and suppressed immune system, compounded by prolonged hospitalization and invasive therapeutic procedures. Aim: The aim of this study was to detect rate of nosocomial pathogens in burned patients with their susceptibility pattern, and to determine the environmental contamination in Burn and plastic surgery department, aljalla hospital, Benghazi. Method: In a prospective study and statistical analysis was performed for 120 samples were collected from different wound sites in burn and plastic surgery department, aljalla hospital during year 2016, additional to 217 samples were collected from patient zones, fl oor areas, walls, bed-frames, door handles, light switches, sinks, besides corridors, tables, autoclave, cupboards, medical waste transport cart, dressing room, nursing station, drums, trolley, nasal and hand swabs for nursing staff, then cultured on blood agar and MacConkey agar, Isolation and identifi cation of microorganisms was done according to standard procedure.